The Role of Auxiliary Verbs in Expressing Aspect in English Compared to Russian - Sulaymonova, Madina Amrullo kizi; Satibaldiyeva, Nigora Alimkul kizi (The Lingua Spectrum, 2026)
This study looks at how English and Russian handle aspects of time in their languages, and honestly, the differences are quite fascinating. It dives into the different ways each language expresses the timing of actions – whether something is ongoing, completed, or just beginning. Both languages deal with similar ideas, but they do it in very different ways, which can be tricky for learners. English tends to be more analytic, using auxiliary verbs like “be” and “have” to carefully build meaning around aspects. You can almost see the language constructing the picture piece by piece. On the other hand, Russian is more synthetic, weaving aspectual differences directly into the verbs through prefixes and suffixes - it feels more immediate, more compact. By comparing these two approaches, the research sheds light on how their unique structures lead to natural variations across languages. The results help clarify how these different grammatical systems manage the complexities of actions and their timing, and hopefully make life a bit easier for anyone trying to master either tongue.